Muscle adaptation while skate skiing with and without poles - Higginson, B. K.; Heil, D. P. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Skate skiing without the use of ski poles is a common training technique utilized by many skiers to improve skate skiing technique and performance. This training technique requires a greater focus on balance and stability throughout the stride cycle. This increased demand for balance and stability, as well as the loss of upper extremity contribution to forward propulsion, results in subsequent changes in muscle function of the upper and lower extremities. Changes in upper and lower extremity muscle recruitment while skate skiing with and without poles has not been previously reported. Therefore, the purpose of this study is to quantify changes in upper and lower extremity muscular function while skate skiing with and without the use of ski poles.